Serum levels of perfluorooctanoic acid and perfluorooctane sulfonic acid in pregnant women: Maternal predictors and associations with birth outcomes in the PIPA Project. Issue 9 (10th June 2021) - Espindola Santos, Aline de Souza; Meyer, Armando; Dabkiewicz, Vanessa Emídio; Câmara, Volney de Magalhães; Asmus, Carmen Ildes Rodrigues Froes
Abstract: Aim: Perfluorooctanoate (PFOA) and perfluorooctane sulfonate (PFOS) are persistent pollutants associated with adverse birth outcomes. This study aimed to identify predictors of blood PFOA and PFOS concentrations in pregnant women and to estimate their associations with birth outcomes in Brazil. Methods: We conducted a cross‐sectional study with 139 pregnant women enrolled in the pilot study of the Rio Birth Cohort Study on Environmental Exposure and Childhood Development (PIPA Project). Multiple linear regression was used to estimate associations between PFOA and PFOS with maternal predictors and birth outcomes. Results: Higher levels of PFOA were observed in women aged 16–19 and 20–39 years, while fish consumption from 0.6 to 2.0 times per week was associated with lower levels of the substance. PFOS levels were higher in women living in houses with up to four rooms but lower in those who reported passive exposure to smoking. Increased newborn length and head circumference were also associated with higher maternal levels of PFOA. Conclusions: In our study, age, fish consumption, passive smoking, and the number of rooms in the house were predictors of maternal PFAS levels. However, we did not observe significant associations between maternal plasma PFAS concentrations and birth outcomes.